FENOMENA PINJAMAN ONLINE ILEGAL: ANALISIS PERATURAN PERUNDANG-UNDANGAN DAN PERLINDUNGAN MASYARAKAT - Ayu Souterya Alkatiri; Wihelmina Ruli Loo; Kristina Desita Angul; Penina Persis Lasibey; Kristiana Lipat Samon; Fadil Mas’ud (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital technology has triggered the widespread emergence of illegal online lending in Indonesia, causing exorbitant interest rates, misuse of personal data, and user intimidation. The OJK PASTI Task Force recorded 8,271 illegal online lending entities blocked as of April 2025, yet new platforms continue to emerge. Although regulations such as POJK No. 77/2016 and the ITE Law are in place, their implementation is hindered by low public digital literacy and the rapid evolution of digital platforms. Previous studies have predominantly examined economic and consumer behavior aspects, and have not comprehensively integrated analysis of legal regulations, digital citizenship education, and preventive protection. This normative legal research, using statutory and conceptual approaches, aims to analyze regulations and legal protection against illegal online lending. The findings indicate that the legal substance is adequate; however, enforcement is impeded by weak interagency coordination, the adaptive nature of illegal platforms, and low public legal awareness. This study recommends integrating digital citizenship education and Pancasila-based digital ethics into the curriculum as a preventive measure, alongside strengthening OJK’s digital surveillance system and cross-institutional cooperation.